Study of Pathway to Care among Patients with Epilepsy - Subedi, S; Shyangwa, PM; Shakya, R; Pandey, AK (Journal of Universal College of Medical Sciences, 2013)
Objective: To assess the pathway to care among patients with epilepsy up to the tertiary care centre Methods: It is a hospital based, cross-sectional descriptive study of 47 patients visiting BPKIHS psychiatry OPD. Written informed consent was taken from the patients and the primary caretaker. A semi structured Performa was used to record the basic sociodemographic details. Pathway Interview Schedule developed by WHO was used to collect the data. Results Majority (66.0%) of subjects were male. Generalized Seizures were most common (76.6%) type of seizure followed by complex-partial seizure (10.6%). More than half (51.1%) first contacted dhami-jhakri for treatment of their illness. About sixty two percent of patients had the first contact with the treatment provider less than 4 yrs ago. Thirty eight percent subjects sought treatment as per advice from the family members while only 2.1% sought treatment as per advice from the healthcare worker. The most common presenting complaints were sudden loss of consciousness in 89.4%of patients. In majority of patients (57.4%), problem arised ≤ 4yrs back. Significant high numbers of patients (51.1%) were prescribed alternative forms of treatment like herbal medications, talisman, offerings and sacrifices and jhadphook for their presenting problem. About eighty seven percent patients had to travel ≤12 hours for the treatment while 10.7% had to travel a distance of >24 hrs for treatment. The mean duration that one had to travel for seeking treatment was 7.95±14.58 hours. It was found that the mean duration that one patient spend before coming to a hospital for modern treatment was 5.64 months. Conclusions People suffering from epilepsy are still using the traditional healing practices leading to delay in the patient care. These findings call for a comprehensive educational program that can remove the misconcepts regarding the illness. DOI: http://dx.doi.org/10.3126/jucms.v1i1.8418 Journal of Universal College of Medical Sciences Vol.1(1) 2013: 20-25